Indentation creep and anisotropy in magnesium oxide and germanium - Everitt, N; Everitt, Nicola Mary (1990)
﻿ Hardness tests have the potential to provide a simple means of investigating the mechanical properties of materials, both at room temperature, and at higher temperatures. However, the information gained can not be fully utilized unless the deformation processes and variables are properly understood. Careful consideration of such deformation on single crystals can help to clarify the situation and lead to better understanding. This thesis describes indentation experiments on (001) MgO and Ge at temperatures up to 1175°C and 700°C respectively. Since anisotropy was one of the questions being addressed, the majority of the testing used Knoop indenters, although a few experiments used Vickers indenters. The work was carried out on a specially commissioned high temperature hardness tester (based on an original design by Wilberforce Scientific Developments). A main conclusion of the discussion on the design of high temperature hardness testers is the importance of independent heating of the indenter for accurate hardness results. The indentation behaviour of MgO was shown to include creep, even at room temperature for the Knoop <110> orientation. However a region of no indentation creep was exhibited between 750°C and 1050°C for both Vickers and Knoop indentations. This has not been reported in previous studies. The anisotropy displayed at room temperature between <110> and <100> Knoop decreased with increasing temperature, due to the faster creep rate of the < 110> orientation, and finally reversed. Knoop indentations in the <110> and <100> orientations on Ge also showed hardness anisotropy which changed with temperature. In this case there was no anisotropy at room temperature, but anisotropy developed as the temperature increased due to the faster creep rate of the <110> orientation. The indentation hardness response of both MgO and Ge is explained in terms of the interaction of dislocation arrays which are formed in the first few moments of the indentation. Measurement of the two diagonals of the Knoop indentations showed that the ratio of the diagonal lengths, and also the morphology of the surrounding material, can be used to examine the extent and direction of material displacement. Surface etching, and etching of sections, were used to analyse the disposition of slip around the indentations.